Keeping the women out: a gendered organizational approach to understanding early career-ending police misconduct - Gaub, Janne E. (Crime & delinquency, 2022)
Female representation in policing has stagnated over the past three decades, even with repeated calls for diversification. One explanation for this is that agency attempts to diversify the workforce are merely perfunctory—departments recruit and hire women to placate reformers, but then remove them at opportune times. Guided by the gendered organizations framework, this study uses secondary data from the New York Police Department (NYPD) to examine the extent to which the NYPD used the discretionary nature of probation to remove women from the ranks. We find that a substantially higher percentage of women (compared to men) were terminated from the NYPD during probation, and for relatively minor offenses. We discuss the theoretical and policy implications of these findings.